Hubungan dukungan keluarga terhadap kepatuhan terapi hemodialisa pada pasien gagal ginjal kronik - Pita Meviyana; Sriyati Sriyati; Hamudi Prasestiyo (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2026)
Background: Chronic kidney disease is a progressive disease that requires lifelong renal replacement therapy, one of which is hemodialysis. Patient compliance in undergoing therapy is very important to prevent complications and improve quality of life. One of the factors that influence compliance is family support. Purpose: To determine the relationship between family support and adherence to hemodialysis therapy in chronic kidney failure patients. Method: Quantitative research with correlational analytical design using a cross-sectional approach. A sample of 73 respondents was selected using a purposive sampling technique. Data were collected using a family support questionnaire and a hemodialysis therapy adherence questionnaire, then analyzed using the Spearman Rank test. Results: The results showed a significant relationship between family support and adherence to hemodialysis therapy with a p value = 0.000 (p <0.05) and a correlation coefficient of r = 0.495. These values ​​indicate a positive relationship with moderate strength, which means that the higher the family support, the higher the patient's adherence in undergoing hemodialysis therapy. Conclusion: There is a significant relationship between family support and adherence to hemodialysis therapy in patients with chronic kidney disease. Optimal family support plays a crucial role in improving patient adherence to hemodialysis therapy and supporting treatment success.   Keywords: Adherence; Family Support; Hemodialysis.   Pendahuluan: Gagal ginjal kronik merupakan penyakit progresif yang memerlukan terapi pengganti ginjal seumur hidup, salah satunya hemodialisa. Kepatuhan pasien dalam menjalani terapi sangat penting untuk mencegah komplikasi dan meningkatkan kualitas hidup. Salah satu faktor yang memengaruhi kepatuhan adalah dukungan keluarga. Tujuan: Untuk mengetahui hubungan dukungan keluarga dengan kepatuhan terapi hemodialisa pada pasien gagal ginjal kronik. Metode: Penelitian kuantitatif dengan desain analitik korelasional menggunakan pendekatan cross-sectional. Sampel sebanyak 73 responden dipilih dengan teknik purposive sampling. Data dikumpulkan menggunakan kuesioner dukungan keluarga dan kuesioner kepatuhan terapi hemodialisa, kemudian dianalisis menggunakan uji Spearman Rank. Hasil: Terdapat hubungan yang signifikan antara dukungan keluarga dan kepatuhan terapi hemodialisa dengan nilai p = 0,000 (p < 0,05) dan koefisien korelasi r = 0,495. Nilai tersebut menunjukkan hubungan positif dengan kekuatan sedang, yang berarti semakin tinggi dukungan keluarga maka semakin tinggi kepatuhan pasien dalam menjalani terapi hemodialisa. Simpulan: Terdapat hubungan yang signifikan antara dukungan keluarga dengan kepatuhan terapi hemodialisa pada pasien gagal ginjal kronik..   Kata Kunci: Dukungan Keluarga; Hemodialisa; Kepatuhan.